A Comprehensive Literature Review of JAK Inhibitors in Treatment of Alopecia Areata - Dillon KAL (Dove Medical Press, 2021)
Kerry-Ann L Dillon 1, 2 1Department of Microbiology, Immunology and Pharmacology, St. George’s University School of Medicine, True Blue, Grenada; 2Department of Dermatology, School of Health, Sport & Professional Practice, Faculty of Life Sciences and Education, University of South Wales, Pontypridd, South Wales, UKCorrespondence: Kerry-Ann L DillonDepartment of Microbiology, Immunology and Pharmacology, St. George’s University School of Medicine, True Blue, GrenadaTel +473 5360369Email k.dillon26@hotmail.comAbstract: Alopecia areata (AA) is a chronic, immune-mediated form of nonscarring alopecia that is multifactorial and results in localized patches. It is often described as a self-limiting condition that results in the spontaneous regrowth of hair in most cases. However, this regrowth may take several months or years to occur in some patients, leading to the development of psychoemotional trauma in those that are affected. Although several therapies for AA have been developed and tested, there is no specific treatment that has been approved, leading to the availability of many off-label conventional treatment options, with very limited responses. More recently, with the advancement of pre-clinical and genetic studies, a greater understanding of the pathomechanisms involved in the development of AA has been uncovered. This has resulted in the introduction of targeted therapies that use small molecules to block specific pathways involved in AA pathophysiology. As such, the use of janus kinase (JAK) inhibitors for treatment of AA has emerged. JAK inhibitors block the T-cell mediated inflammatory response thought to be the driving factor behind AA pathogenesis, by inhibiting the janus kinase (JAK) signal transducer and activator of transcription (STAT) signaling pathway, leading to a reversal of hair loss in AA patients. Thus, in an effort to demonstrate the efficacy of JAK inhibitors in the treatment of AA, several studies have been published within recent years. However, the question remains, “Are JAK inhibitors effective and safe in the management of Alopecia Areata?”. This review aims to provide a comprehensive report on the role, efficacy, and outcomes of using JAK inhibitors in the treatment of AA. To competently answer the research question highlighted, the most recent, quality articles published over a 10– 15-year period were sourced using PubMed, NCBI, Research gate, Medline, Cochrane Central Register of Controlled Trials, EMBASE and Google scholar. The literature search was primarily focused on randomized controlled trials (RCTs); however, in the absence of such, only the most recently published case reports, case series, clinical trials and open-label studies published to date were included.Keywords: janus kinase, JAK-STAT signaling pathway, ruxolitinib, tofacitinib, baricitinib